Site selection for seaweed culture at Gerupuk Bay - West Nusa Tenggara using remote sensing and GIS - Nirmala, Kukuh; Ratnasari, Arlina; Budiman, Syarif (Jurnal Akuakultur Indonesia, 2014)
ABSTRACT Site selection for seaweed culture faces some problems that require more cost, time, and energy. Technology such as remote sensing and geographic information systems (GIS) were regarded as good solutions for site selection to increase seaweed culture. The aim of this study was to analyze suitable location for seaweed culture at Gerupuk Bay, West Nusa Tenggara. The site selection used Landsat 8 satellite with sea surface temperature (SST), total suspended matter (TSM), and protected location as the parameters. Each parameters were processed using Er Mapper 7.0 software and then Arcview GIS 3.2 software to create the thematic GIS map. Site selection for seaweed culture could be determined by maps overlay technique. The results of this study showed that the most suitable site for seaweed culture at Gerupuk Bay was 342.44 ha (25.22%), moderate suitable site was 190.78 ha (14.05%), and unsuitable site was 669.32 ha (49.3%). Keywords: GIS, remote sensing, location suitability, seaweed culture  ABSTRAK Penentuan lokasi budidaya rumput laut sering mengalami kendala yang membutuhkan banyak biaya, waktu, dan tenaga. Teknologi berupa penginderaan jauh (inderaja) dan sistem informasi geografis (SIG) menjadi solusi yang baik dalam penentuan lokasi yang sesuai untuk pengembangan budidaya rumput laut. Penelitian ini bertujuan untuk menganalisis kesesuaian lokasi budidaya rumput laut perairan Teluk Gerupuk, Nusa Tenggara Barat. Penentuan kesesuaian lokasi budidaya rumput laut menggunakan citra satelit Landsat 8 dengan parameter suhu permukaan laut (SPL), muatan padatan tersuspensi (MPT), dan keterlindungan. Parameter tersebut diolah menggunakan perangkat lunak Er Mapper 7.0 kemudian dilakukan pengolahan SIG menggunakan perangkat lunak Arcview GIS 3.2 sehingga dihasilkan peta tematik. Peta tematik tersebut ditumpang susun sehingga dihasilkan peta kesesuaian lokasi budidaya rumput laut. Hasil penelitian ini menunjukkan bahwa lokasi yang sesuai untuk budidaya rumput laut di Teluk Gerupuk adalah 342,44 ha (25,22%), luas lokasi cukup sesuai adalah 190,78 ha (14,05%), dan luas lokasi tidak sesuai adalah 669,32 ha (49,3%). Kata kunci: SIG, penginderaan jauh, kecocokan lokasi, budidaya rumput laut